Kajian Kompetensi dan Orientasi Terhadap Kinerja Usaha (Survei Tentang Kewirausahaan Simping Wanita di Kabupaten Purwakarta) - Dadang Munandar (Universitas Komputer Indonesia, 2022)
Knowing the effect of competence and entrepreneurial orientation on business performance in Simping entrepreneurs among women in Purwakarta Regency is the purpose of this study. In this study, researchers used quantitative research with survey methods. There were 90 women entrepreneurs as samples which were selected purposively. Path analysis was used as an analytical technique. This research resulted in competence and orientation variables that affect business performance positively and significantly simultaneously. Furthermore, the competence variable affects business performance positively and significantly partially and in the same way orientation affects business performance positively and significantly. Meanwhile, the entrepreneurial business performance of female Simping has decreased because the competence of the workforce is not in accordance with the development of the demands of the current business world. Accordingly, it can be conluded that the Simping female entrepreneurs’ competence and orientation give an effective effect in enhancing the performance to manage their business. Key Words : competence, female entrepreneur, orientation, performance